Editorial - Editor, Executive (Ushus Journal of Business Management, 2005)
The seven papers published in this edition of Ushus have a wide ranging scope by various academicians, professionals and researchers with varying areas of interest. The first paper is on the ’Health Care System in Goa: Analysis of Role in Sustainable Development’ by Anna Rovina Ferrao e Fernandes. It offers an in-depth study of a unique approach of Health Care in aiding sustainable development. The second paper by Triveni S. and Vijayalaxmi A. Amminabhavi is ’A Study of Quality of Work Life of Nationalised and Non Nationalised Bank Employees’. It is relevant and contemporary as it highlights the shifted focus of work-life balance and issues relating to job satisfaction. Rev. S. Peter, K.J. Raman and R Ravilochanan have drafted a detailed analysis of ’The Role of Non-governmental Organisations in Minimising School Dropouts’. Further, A. Abdulraheem and A. Raman’s study of the ’Descriptive Model of Community Participation: Delivering Urban Service’ is extremely exhausting in terms of coverage. Given the same, both these papers tackle new-age issues in a rapidly changing socio-economy driven by concerns from the local to the global level and influenced by numerous factors of modernisation. ’Dynamics of Rupee Convertibility’ by V.K. Xavier and ’Employee Attitude Surveys: A Powerful Tool for Enhancing Organisational Effectiveness’ by Rashmi Nakra deal with conventional subjects of study in the domain of International Finance/Forex and statistical value in managerial decision making. The last paper by P.A. Mathew deals with ’Diaspora to Transnational Networks: The Case of Chinese Diaspora in the Mainland China’. It stands out as a subject of modern interest given the role of diaspora in third world and developed economies, especially the Asian continent.